2018
DOI: 10.1177/000313481808400638
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Surgical Site Infections after Thyroid and Parathyroid Surgery: No Role for Antimicrobial Prophylaxis

Abstract: To better define the value of antimicrobial prophylaxis (AMP) and antiseptic skin preparation (ASP) in thyroid and parathyroid surgery, we examined the rate of surgical site infections (SSIs) with and without AMP. Retrospective analysis was performed using the National Surgical Quality Improvement Program database at a single institution. Patients undergoing thyroid or parathyroid surgery with data entered into the National Surgical Quality Improvement Program database at our institution between November 2007 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…9 The length of follow-up was reported in 4 studies, and 3 studies clearly indicated the adopted criteria for SSI diagnosis. [7][8][9] As reported in Table 5 and summarized in Figure 2, the overall rate of SSIs was 0.6% in the case group (range, 0.1%-3.8%) and 0.4% in the control group (range, 0.3%-3.4%); this difference was not statistically significant. There was no evidence of heterogeneity (Q = 8.36, P = .138; I 2 = 40.17, indicating low grade of heterogeneity).…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…9 The length of follow-up was reported in 4 studies, and 3 studies clearly indicated the adopted criteria for SSI diagnosis. [7][8][9] As reported in Table 5 and summarized in Figure 2, the overall rate of SSIs was 0.6% in the case group (range, 0.1%-3.8%) and 0.4% in the control group (range, 0.3%-3.4%); this difference was not statistically significant. There was no evidence of heterogeneity (Q = 8.36, P = .138; I 2 = 40.17, indicating low grade of heterogeneity).…”
Section: Resultsmentioning
confidence: 80%
“…Accordingly, 3 studies were RCTs 5,6,9 and 3 were non-RCTs. 7,8,10 Furthermore, 3 studies were conducted in Europe, 2 in Asia, and 1 in the United States; none of the studies had been published in Africa or South America. Only 1 study was multicentric, 5 involving 4 centers, whereas the others were based on a single center.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the availability of new studies published on the subject [13][14][15], we conducted a systematic review of the most recent evidence with the aim to guide clinical practice.…”
Section: Introductionmentioning
confidence: 99%